KNOWLEDGE MANAGEMENT FOR LAND DEGRADATION MONITORING AND ASSESSMENT: AN ANALYSIS OF CONTEMPORARY THINKING. (17th June 2011) - Reed, M. S.; Fazey, I.; Stringer, L. C.; Raymond, C. M.; Akhtar‐Schuster, M.; Begni, G.; Bigas, H.; Brehm, S.; Briggs, J.; Bryce, R.; Buckmaster, S.; Chanda, R.; et al.
ABSTRACT It is increasingly recognised that land degradation monitoring and assessment can benefit from incorporating multiple sources of knowledge, using a variety of methods at different scales, including the perspectives of researchers, land managers and other stakeholders. However, the knowledge and methods required to achieve this are often dispersed across individuals and organisations at different levels and locations. Appropriate knowledge management mechanisms are therefore required to more efficiently harness these different sources of knowledge and facilitate their broader dissemination and application. This paper examines what knowledge is, how it is generated and explores how it may be stored, transferred and exchanged between knowledge producers and users before it is applied to monitor and assess land degradation at the local scale. It suggests that knowledge management can also benefit from the development of mechanisms that promote changes in understanding and efficient means of accessing and/or brokering knowledge. Broadly, these processes for knowledge management can (i) help identify and share good practices and build capacity for land degradation monitoring at different scales and in different contexts and (ii) create knowledge networks to share lessons learned and monitoring data among and between different stakeholders, scales and locations. Copyright © 2011 John Wiley & Sons, Ltd.